Effect of the COVID-19 pandemic on the ability of level 1 trauma centers to meet American College of Surgeons research requirements. Issue 1 (24th February 2021) - Madayag, Robert M; Sercy, Erica; Berg, Gina M; Banton, Kaysie L; Carrick, Matthew; Lieser, Mark; Tanner, Allen; Bar-Or, David
Abstract : Introduction: The COVID-19 pandemic has had major effects on hospitals' ability to perform scientific research while providing patient care and minimizing virus exposure and spread. Many non-COVID-19 research has been halted, and funding has been diverted to COVID-19 research and away from other areas. Methods: A 28-question survey was administered to all level 1 trauma centers in the USA that included questions about how the pandemic affected the trauma centers' ability to fulfill the volume and research requirements of level 1 verification by the American College of Surgeons (ACS). Results: The survey had a 29% response rate (40/137 successful invitations). Over half of respondents (52%) reported reduced trauma admissions during the pandemic, and 7% reported that their admissions dropped below the volume required for level 1 verification. Many centers diverted resources from research during the pandemic (44%), halted ongoing consenting studies (33%), and had difficulty fulfilling research requirements because of competing clinical priorities (40%). Discussion: Results of this study show a need for flexibility in the ACS verification process during the COVID-19 pandemic, potentially including reduction of the required admissions and/or research publication volumes. Level of evidence: Level IV, cross-sectional study.